How to extend your Victorian terraced house - Green, Jaqueline (London : RIBA Publishing, 2020)
Packed with detailed plans and ideas for a range of house types and sizes, along with photos and 3D sketches, this book provides you with all the design inspiration and advice needed to embark on a Victorian terrace renovation. Case studies of various Victorian terrace house types reveal, floor by floor, a range of options for extending and/or rearranging the space, alongside practical guidance on rules of thumb' for design and information on permitted development rights. Colour-coded before-and-after plans show at a glance which walls have been removed or changed in each option, and all plans have been drawn to scale so that they may be measured from and used when planning your own home renovation project.
Case Study 5 THE TALL TERRACE: a three-storey house with entrance at street level -- Case Study 6 THE SPLIT LEVEL: a three-storey house with its entrance floor above street level -- Case Study 7 THE LARGE SEMI: a large, three-storey house with an upper and lower ground-floor level -- Conclusion -- Index -- Image Credits
OCLC-licensed vendor bibliographic record.
Keywords: Terrace houses; Row houses; Architecture, Domestic -- Conservation and restoration; Architecture, Victorian -- Great Britain; ARCHITECTURE / Design & Drafting